2007
DOI: 10.1295/polymj.pj2007091
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Carbon Fiber Fabrics from Phenolic Resin by Electrospray Deposition

Abstract: ABSTRACT:Flexible carbon fiber fabrics of 1.7 mm diameter fiber were prepared by electrospray deposition (ESD) from phenolic resin/poly(vinyl butyral) and successive curing and carbonization. In the present study, phenolic resin (thermostable 3-dimensional cross-linked polymer) was used for ESD and successive carbonization. The bead-free fiber was obtained by ESD from a phenolic resin solution with concentration above 55 wt %. The as-deposited fabrics, however, were very brittle. The addition of poly (vinyl bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…To overcome this disadvantage, we have reported the preparation of novolac phenolic resin-based carbon fabrics composed of microscaled fibers by electrospinning. 9 The major advantage of the phenolic resin as the precursor of the carbon fibers is thermal stability leading to a dimensional stability after carbonization (curing of the as-spun fibers also improves the thermal stability). Another advantage is the high microporosity of the carbonized fibers (phenolic resin is well-known as a material for activated carbon).…”
mentioning
confidence: 99%
“…To overcome this disadvantage, we have reported the preparation of novolac phenolic resin-based carbon fabrics composed of microscaled fibers by electrospinning. 9 The major advantage of the phenolic resin as the precursor of the carbon fibers is thermal stability leading to a dimensional stability after carbonization (curing of the as-spun fibers also improves the thermal stability). Another advantage is the high microporosity of the carbonized fibers (phenolic resin is well-known as a material for activated carbon).…”
mentioning
confidence: 99%
“…Figure 3(a) and 3(b) shows the electrospun fibres were discontinuously formed for both PF and BPF resin. This could be due to the low molecular weight of polymer solution (Suzuki et al 2007). At lower molecular weight, the fibre structure was not completely uniform and tends to form bead-on-string structure thus the fibre diameter increased with the increasing of solution's molecular weight (Koski et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…It is a high-molecular-weight polymer in the range of (170,000 -250,000) that helped improve the fibre formation as PVB showed good compatibility with phenolic resin (Suzuki et al 2007). Imaizumi et al (2009) reported that PVB could improve the electrospinnability by adjusting the solution viscosity (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These resins have interesting properties that make them suitable for industrial use, such as thermostability and mechanical strength. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] During the curing of novolacs, hexamethylenetetramine (HMTA) is frequently used as the curing agent; 1 however, the resultant curing products usually tend to contain amine derivatives and the unreacted curing agent as impurities, which often lead to coloration and degradation of the products.…”
mentioning
confidence: 99%